Special Issue "HPV in the Head and Neck Region 2.0" - Dalianis Tina; von Buchwald Christian; Näsman Anders; Syrjänen Stina (MDPI, 2025)
Members of the human papillomavirus (HPV) family have been known for causing cancers and condylomas in the anogenital tract for some time, as reflected by the Nobel Prize in Medicine given to Professor Harald zur Hausen 2008 [...].